Kontribusi Daya Ledak Otot Tungkai Terhadap Ketepatan Smash Bola Voli Putra pada Club Surya Bakti Padang (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The low smash accuracy of male volleyball athletes from Surya Bakti Padang Club is thought to be related to the athletes' physical condition, one of which is the explosive power of the leg muscles. This study aims to analyze the relationship between explosive power of the leg muscles and smash accuracy and to identify the statistical contribution of explosive power of the leg muscles to smash accuracy in male volleyball athletes from Surya Bakti Padang Club. The study used a quantitative approach with a correlational design. The study sample consisted of 15 male volleyball athletes selected using a purposive sampling technique. Data were collected using the Vertical Jump Test to measure explosive power of the leg muscles and a smash accuracy test to measure smash accuracy. Data analysis included normality tests, homogeneity tests, Product Moment correlations, significance tests, and coefficients of determination. The results showed a very strong positive relationship between explosive power of the leg muscles and smash accuracy, with a coefficient of determination of 94.5%, indicating a large variation in smash accuracy that was statistically related to explosive power of the leg muscles in the study sample. These findings indicate that the development of explosive power of the leg muscles can be one aspect that needs to be considered in developing a training program to support the improvement of smash accuracy, although other physical and technical factors also have the potential to influence this ability.